E‐cigarette or vaping product use associated lung injury (EVALI) in the time of COVID‐19: A clinical dilemma. Issue 3 (17th January 2022) - Helfgott, Daniel; Capozzoli, Gabrielle; Madray, Jovanna; Baig, Aisha; Uppaluri, Lakshmi; Gaur, Sunanda; Simon, Mitchell; Amorosa, Judith; Ramagopal, Maya
Abstract: Aim: To report on the clinical, laboratory, and radiological findings of adolescents who presented during the SARS‐CoV‐2 surge with symptoms of Coronavirus disease 2019 (COVID‐19), did not test positive for the infection, and were diagnosed with E‐cigarette and vaping product use associated lung injury (EVALI). Methods: A retrospective review of 12 cases of EVALI admitted to the Bristol Meyers Squibb Children's Hospital between February 2020 and June 2020 was conducted. Results: The ages of the patients ranged from 14 to 19 years. There were six males and six females. Three patients had a past history of anxiety, depression, or other psychiatric/mental health disorder, 9 had prolonged coagulation profile (prothrombin time, partial thromboplastin time,  and/or International Normalized Ratio), and 11 had elevated inflammatory markers. Eight needed respiratory support. All 12 were negative for SARS‐CoV‐2 PCR. Four were tested for IgG antibodies and were negative. As these cases were admitted to rule out COVID infection, initial treatment included hydroxychloroquine. Steroids were started only after SARS‐CoV‐2 PCR was shown to be negative. Urine tetrahydrocannabinol was positive in all cases. Chest X‐ray and computed tomography findings showed ground glass opacities. Conclusions: Clinical and radiological features are similar in both EVALI and SARS‐CoV‐2 infection. Inflammatory markers are elevated in both conditions. A detailed social and substance use history in patients presenting with "typical" COVID pneumonia like illness is important. EVALI should be ruled in early to start the appropriate treatment. Given the ongoing pandemic, pediatricians and other health‐care providers need to be aware of other conditions that can masquerade as SARS‐CoV‐2.